KORELASI ANTARA INTEGRITAS TERAPI MUSIK DENGAN TINGKAT EKSPRESI EMOSI MAHASISWA - Astri Ramadani; A. Ainun Fadillah; Nur Aulia Rahma; Nurhikma; Abdul Hakim; Citra Prasiska Puspita Tohamba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between the intensity of music therapy and the level of emotional expression of students at Makassar State University. The phenomenon of increasing academic, social, and personal pressures causes many students to experience difficulties in expressing emotions healthily. Music is seen as an alternative medium to help regulate and channel emotions. This study uses a quantitative approach with a non-experimental correlational method. The study population consisted of students of the Guidance and Counseling Study Program at Makassar State University, with data collection through a courage questionnaire. Data analysis was carried out using descriptive tests, the Kolmogorov-Smithnov normality test, simple linear regression, and the Pearson correlation test. The results of this study indicate a positive and significant relationship between the intensity of music therapy and the level of emotional expression of students (r = 0.429; p = 0.001). This means that the higher the intensity of students in music therapy, the higher their ability to express emotions adaptively. Music therapy has been shown to stimulate the autonomic nervous system, reduce stress, and improve emotional well-being. These findings support the application of music therapy as an effective nonverbal therapy in guidance and counseling, especially to help students manage emotions and mental health positively.